Catechisme Historique ou Explication Complete du Catechisme - Belet, M. L'abbe P. (Librairie de Louis Vives, Editeur, 1860)
Stamp of St. Joseph Seminary
Keywords: 1.Conservation 保護; 10.Cover Damage; 14.missing area; 18.Bookworm; 2.Damage